1992
DOI: 10.1210/endo.131.1.1612027
|View full text |Cite
|
Sign up to set email alerts
|

Transport of 3,5,3'-triiodothyronine into the perfused rat liver and subsequent metabolism are inhibited by fasting.

Abstract: The effects of 48-h fasting on transport of T3 and subsequent metabolism in the isolated perfused rat liver were investigated. Tracer T3 disappearance curves from the recirculating medium consisted of a fast component (FC) and a slow component (SC). Using a two-compartment model, both transport [expressed as the fractional transport rate constant from medium to liver (k21)] and disposal of T3 were calculated. After fasting, k21, total metabolism, and metabolism corrected for differences in mass transfer were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This does not agree with the present study, however, the difference in culture systems between the studies suggests that the effects observed are related to culture conditions. Transmembrane movement of THs was thought to be a passive process; however, there is evidence that translocation occurs through active transport mechanisms (Blondeau et al, 1988;De Jong et al, 1992. Specifically, members of the MCT and OATP family have been shown to facilitate TH transport (Friesema et al, 2003(Friesema et al, , 2008Pizzagalli et al, 2002;van der Deure et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This does not agree with the present study, however, the difference in culture systems between the studies suggests that the effects observed are related to culture conditions. Transmembrane movement of THs was thought to be a passive process; however, there is evidence that translocation occurs through active transport mechanisms (Blondeau et al, 1988;De Jong et al, 1992. Specifically, members of the MCT and OATP family have been shown to facilitate TH transport (Friesema et al, 2003(Friesema et al, , 2008Pizzagalli et al, 2002;van der Deure et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Energy dependency of thyroid hormone transport in hepatocytes is not only found in vitro , but also in the perfused intact rat liver and in humans. When livers of starved rats are perfused using T 4 or T 3 as a substrate, a decrease in uptake is found ( Jennings et al ., 1979 ; De Jong et al ., 1992 ). Preperfusion of these livers with a combination of insulin plus cortisol and/or glucose restores uptake to normal within 1/2 h suggesting that no protein synthesis is involved.…”
Section: Thyroid Hormone Plasma Membrane Transport Is Subject To Regumentioning
confidence: 99%
“…The effects of fasting on thyroid hormone uptake into the liver can be investigated in vivo (Van der Heyden et al 1986, De Jong et al 1994 or in the perfused liver (De Jong et al 1992, and experiments with hepatocytes can be performed 4 h after plating (Lim et al 1993a, b, Vos et al 1995, but it is more complicated to study the effects of fasting on thyroid hormone uptake into the pituitary. In vivo measurements and adequate perfusion experiments are excluded for practical reasons, and studies in cultured cells require at least 2 days to permit attachment of the cells (Everts et al 1993(Everts et al , 1994a(Everts et al , 1995a; consequently, effects on the pituitary induced by in vivo treatment may disappear during prolonged culture of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…In perfused liver, both acute energy depletion (De Jong et al 1994) and prolonged fasting (De Jong et al 1992) resulted in a decrease in thyroid hormone transport. These observations support the view that the thyroid hormone uptake mechanism is energy-dependent both in the pituitary and in the liver, whereas the long-term regulation of the thyroid hormone transport capacity in the two organs is different under conditions associated with a reduction in plasma T 3 (see also Everts et al 1996).…”
Section: Energy Status Bilirubin and Pituitary Function · F W J S Wamentioning
confidence: 99%
See 1 more Smart Citation